Model Analisis Tahap Rentan Kawasan Banjir untuk Lembangan Sungai Pahang (An analysis model for flood susceptibility areas in Sg Pahang river basin) - Asmawi, M. Zainora; Ibrahim, Illyani (2018)
This model was developed using ArchGIS system to study on the flood susceptibility area in the catchment of Sg Pahang river basin. It was designed by using five factors that was defined from literature review; (topographic & DEM, slope, land use, distance from the river and ARI for flood). All of these factors are processed using weightage to prepare a susceptibility map for Sg Pahang river basin.